2014
DOI: 10.1007/978-1-4939-0888-2_6
|View full text |Cite
|
Sign up to set email alerts
|

The Greatwall–PP2A Axis in Cell Cycle Control

Abstract: Cell cycle progression is largely controlled by reversible protein phosphorylation mediated by cyclically activated kinases and phosphatases. It has long been known that cyclin B-Cdk1 activation triggers mitotic entry, and the enzymatic network controlling its activation and inactivation has been well characterized. Much more recently protein phosphatase 2A (PP2A) together with its B55 regulatory subunit has been recognized as the major activity dephosphorylating Cdk1 targets. Moreover, PP2A-B55 activity is hi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 59 publications
1
12
0
Order By: Relevance
“…Despite a long history of research, the mechanism that regulates PP2A-B55 α activity during cell-cycle progression is still poorly understood. The only key regulator identified to date is Greatwall kinase (also known as MASTL) [44][45][46] . In the current study, GRPEL1 appears to constitute a novel mechanism for inhibiting PP2A-B55 α activity during damaged mitosis through direct protein-protein interactions.…”
Section: Discussionmentioning
confidence: 99%
“…Despite a long history of research, the mechanism that regulates PP2A-B55 α activity during cell-cycle progression is still poorly understood. The only key regulator identified to date is Greatwall kinase (also known as MASTL) [44][45][46] . In the current study, GRPEL1 appears to constitute a novel mechanism for inhibiting PP2A-B55 α activity during damaged mitosis through direct protein-protein interactions.…”
Section: Discussionmentioning
confidence: 99%
“…The results suggested that the model required revision to consider not just mitotic cyclin-Cdk levels, but the balance between Cdk and counteracting phosphatase (Cdc14 in budding yeast). Phosphatase PP2A-B55 may play a similar role in some animal systems (Wang et al, 2011). These phosphatases are regulated to be highly active only at the time of mitotic exit, providing an additional (but organism-specific) regulatory loop (not illustrated in Figure 1).…”
Section: Cell-cycle Control In Opisthokontsmentioning
confidence: 99%
“…27,28 As such, the Greatwall-PP2A network has been proposed as a key signaling axis that promotes normal Cdk1-driven entry through mitosis. 29 PP2A also acts on other mitotic mediators, including the key mitosis-specific kinase, Polo-like kinase 1 (PLK1), which localizes to centrosomes during mitosis and when inactivated by PP2A is an important hallmark of G2/M arrest and activation of the DNA damage response. 30 PP2A also participates in a negative feedback loop, antagonizing Aurora B and Plk1 kinases, thus maintaining the spindle assembly checkpoint until microtubules are properly attached to chromosome kinetichores.…”
Section: Inhibition Of Wnt/beta-catenin Signalingmentioning
confidence: 99%